Supporting Policy Reform from the Outside - Smets, Lodewijk (Published by Oxford University Press on behalf of the World Bank, 2021)
Sound economic and social policies are important if countries wish to prosper and achieve sustainable development. It is far from guaranteed, however, that policymakers select and implement good policies, which provides a rationale for external policy support. Indeed, many organizations are engaged in supporting policy reform processes in recipient countries. This study investigates the limits and opportunities of supporting policy reform by focusing on four dimensions of support: conditional financing, policy dialogue, technical evidence and political institutions. Four findings follow from a review of the literature. First, without commitment on the recipient side, conditional financing is unlikely to induce policy reform. Second, when external actors acquire a seat at the policy dialogue table, it is important to detect (and influence) the beliefs policymakers hold. Third, outside parties should bring sound evidence to the table about the costs, benefits, and effectiveness of their policy proposals. Finally, supporting changes in political institutions without considering general equilibrium effects can be counterproductive. The study concludes with a discussion and some avenues for future research in this field.